Pelatihan Sistem Informasi Manajemen Kurban Untuk Meningkatkan Tata Kelola Administrasi Pelaksanaan Kurban - Falah, Syaikhul; Rofingatun, Siti; Waromi, Juliana; Meininta Nababan, Dytha (UNIVERSITAS CENDERAWASIH, 2025)
The annual implementation of the Qurban requires efficient and transparant administrative management to ensure the smooth distribution of meat. To this end, a Qurban Management Information System (SIM) training was held on May 29-30, 2025, at the Roudhatul Jannah Mosque, Jayapura Hajj Dormitory. This community services aimed to improve the capacity of mosque administrators and Qurban committees in digital administrative management. This training combined theoretical and practical approaches, covering the basic concepts of the Qurban Management Information System (SIM), meat distribution strategies, and hands-on practice using digital applications. Participants included mosque administrators, Qurban committee members, and representatives of religious institutions in Jayapura. Evaluation results showed a significant increase in participants' understanding, with testimonials expressing confidence in managing Qurban digitally. The training's impact is expected to include increased transparency, time efficiency, and data accuracy in Qurban implementation. Going forward, similar training is planned to be expanded to other mosques and institutions in Papua to encourage more professional and technology-based Qurban management. The implementation of the Qurban Management Information System (SIM) not only increases accountability but also strengthens public trust in Qurban management institutions. Keywords: Management Information System, Sacrifice, Administrative Governance, Digitalization, Transparency.